Winieta latarni morskiej w La Coruña na mapie Beatusa z Burgo de Osma w kontekście symboliki wczesnochrześcijańskiej - Kochanek, Piotr (Vox Patrum, 2019)
The purpose of this article is to compare the vignette of the lighthouse of La Coruña, which is on the map of Beatus from Burgo de Osma, with the lighthouses carved on reliefs of sarcophagi and tombstones in the epoch of the Roman Empire and with the vignettes of this lighthouse on other surviving medieval maps. In this way, to point out the ideological kinship between these elements. The lighthouse on the reliefs of pagan sarcophagi is the symbol of the happy port to which the human soul is heading. In turn, the lighthouse on Christian grave plates, found in the Roman catacombs, is a symbol of salvation, sometimes treated as the equivalent of the cross. The lighthouse on the map of Burgo de Osma is located on the western border of the world known at that time, which areas were the most remote from both the garden in Eden in the East and from Jerusalem, the place of salvific work of Christ. So these were areas of spiritual darkness, where, according to tradition, Jakub the Elder brought the light of the Gospel. With his arrival, in the areas where death reigned so far, the hope of salvation flared, which is illustrated graphically on the analyzed Beatus map by the lighthouse, which is near the Apostle’s sanctuary. In this way, a safe spiritual haven was first established on the western periphery of the then known world, which over time became a great pilgrimage center. It is no coincidence that this map was made in the circle of the monastic Benedictine culture, which carefully preserved the old Christian tradition.